Intelligence student advising system - an implementation using object-oriented C++ - Abg. Jawawi, Dyg. Norhayati (Penerbit UTM Press, 1997)
This paper present an approach for developing a consistent student course-advising system for undergraduate students using knowledge-based technology. A prototype system has been implemented in object-oriented technique using C++. The prototype system was designed for undergraduate Computing students. The prototype is able to give consultation and advice on some important aspect of student advising problems. Knowledgeable behaviour was produced where the ‘expert’ and ‘knowledge’ is stored separately from the inference engine. Object-oriented programming technique was found to enhance the development of the system.